Enzymatic Profiling of Actinomycetes Isolated From Soil Samples of Chitwan - Bajracharya, Anup Muni; Upadhayaya, Anjali; Shrestha, Anisha; Gurung, Sagun (Journal of Balkumari College, 2024)
This study explores the isolation and characterization of actinomycetes from soil samples in Chitwan, Nepal, focusing on their enzymatic activities and potential industrial applications. Actinomycetes, a group of Gram-positive, filamentous bacteria, are known for their ability to produce a variety of bioactive compounds and industrially significant enzymes. Sixteen soil samples were collected from different areas, resulting in the isolation of 31 actinomycete strains. These isolates were characterized macroscopically and microscopically, followed by biochemical and physiological tests to assess their enzyme production and tolerance to temperature and salt concentrations. The study found that many isolates produced enzymes such as amylase, cellulase, gelatinase, lecithinase, and urease. Additionally, the isolates demonstrated varying degrees of tolerance to different temperatures and salt concentrations. The findings underscore the rich potential of actinomycetes from Chitwan for industrial applications, particularly in producing robust enzymes with desirable properties.